An analysis of combined COMPASS/BeiDou-2 and GPS single- and multiple-frequency RTK positioning - Odolinski, R.; Teunissen, Peter; Odijk, Dennis (INST NAVIGATION, 2013)
The COMPASS/BeiDou-2 Navigation Satellite System from China has attained regional operational status and is expected to reach the same level of popularity as GPS one it has reached its full constellation. Already now Australia is a beneficiary of the regional COMPASS configuration as enough satellites are available to perform Positioning, Navigation and Timing (PNT). This contribution considers combined COMPASS-GPS single point positioning (SPP), relative code positioning and single- and multiple-frequency single-baseline RTK, in Western Australia, Perth. A combined system increases the redundancy and thus allows for more precise position estimates, improved reliability and robustness against failure of any of the systems. We will compare its performance with that of COMPASS- and GPS-only. For single-baseline RTK, we focus our attention on single-epoch ambiguity resolution with the advantage that the system becomes independent of cycle slips. The performance is evaluated by ambiguity success-rates and by comparing the estimated positions to very precise benchmark coordinates. We make use of the LAMBDA method for integer ambiguity resolution, in combination with the Fixed Failure-rate Ratio Test to validate the resolved ambiguities. It will be shown that the increased strength of the combined model allows for improved ambiguity resolution performance and increased positioning robustness and accuracy over the COMPASS- and GPS-only solutions.